Selective Targeting of High‐Affinity LFA‐1 Does Not Augment Costimulation Blockade in a Nonhuman Primate Renal Transplantation Model. Issue 5 (27th January 2017) - Samy, K. P.; Anderson, D. J.; Lo, D. J.; Mulvihill, M. S.; Song, M.; Farris, A. B.; Parker, B. S.; MacDonald, A. L.; Lu, C.; Springer, T. A.; Kachlany, S. C.; Reimann, K. A.; et al.
Abstract : Costimulation blockade (CoB) via belatacept is a lower‐morbidity alternative to calcineurin inhibitor (CNI)‐based immunosuppression. However, it has higher rates of early acute rejection. These early rejections are mediated in part by memory T cells, which have reduced dependence on the pathway targeted by belatacept and increased adhesion molecule expression. One such molecule is leukocyte function antigen (LFA)‐1. LFA‐1 exists in two forms: a commonly expressed, low‐affinity form and a transient, high‐affinity form, expressed only during activation. We have shown that antibodies reactive with LFA‐1 regardless of its configuration are effective in eliminating memory T cells but at the cost of impaired protective immunity. Here we test two novel agents, leukotoxin A and AL‐579, each of which targets the high‐affinity form of LFA‐1, to determine whether this more precise targeting prevents belatacept‐resistant rejection. Despite evidence of ex vivo and in vivo ligand‐specific activity, neither agent when combined with belatacept proved superior to belatacept monotherapy. Leukotoxin A approached a ceiling of toxicity before efficacy, while AL‐579 failed to significantly alter the peripheral immune response. These data, and prior studies, suggest that LFA‐1 blockade may not be a suitable adjuvant agent for CoB‐resistant rejection. Abstract : This study examines the use of belatacept with either depletion or inhibition of the high‐affinity form of LFA‐1 in a nonhuman primate model of kidney transplantation.